A step towards Smart Agriculture System - Mohammed Ridha H .Alhakeem (Green Publisher Indonesia, 2021)
Iraq is built on agriculture. As a result of population growth, accidents, and contamination, India's agriculture sector is currently declining in quality. Therefore, despite the speed and accuracy of the work, we have attempted to simplify the agriculture industry and restrict human involvement. In order to make this a reality, we are using IOT as the regulator and a few sensors that are connected to it. A rancher must occasionally screen the field for a respectable yield. This paper focuses on crop observation using IoT devices that would provide ranchers with real-time field data. Once obtained, the information is evaluated and documented for further use. This task was assigned to increase harvest efficiency and take preventive action against production loss. Additionally, we included a coordinated structure for waste administration. By enabling brilliant activity that is satisfying and independent, the Internet of Things (IOT) has been playing an awesome role in simplifying human lives. Comparing the suggested framework to the current garbage assortment framework, the movement distance is reduced by 30% on average in the approved circumstance. By enabling continuous observation and an optimized route, it reduces the cost of fuel and human labor, upgrading and improving the system.